Faktor Penyebab Trauma Maksilofasial pada Masa Sebelum dan Saat Pandemi COVID-19 - Tetelepta, Glady A.; Leman, Michael A.; Gunawan, Paulina N. (Universitas Sam Ratulangi, 2021)
Abstract: Maxillofacial trauma can be caused by various external and internal factors. The intervention to prevent the COVID-19 pandemic has caused changes in community social activities that contributes to the factors causing maxillofacial trauma during the pandemic. This study was aimed to obtain the factors that caused maxillofacial trauma before and during the COVID-19 pandemic. This was a literature review study using three databases, namely Google Scholar, Pubmed, and ClinicalKey, and the keywords